2009
DOI: 10.1590/s0036-46652009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of human toxocariasis in a rural population from Cajamarca, Peru determined by DOT-ELISA test

Abstract: SUMMARYThe aim of this study was to estimate the frequency of human toxocariasis in Cauday district, Cajamarca, Peru, using a dot-ELISA test. From June to October 2005, a total of 256 adult subjects were studied. Blood samples were collected for serology by a dot-ELISA test and for hematological examination. Parasitological examination was also carried out in stool samples to check cross-reactions in the dot-ELISA. The frequency observed was 44.92%, with a significant higher proportion of positivity in male su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 32 publications
3
26
1
6
Order By: Relevance
“…This value is among the values of frequency previously found in other places from our country [7][8][9]30,31 and relatively similar with other studies from other Latin American countries 2,3,21,27 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This value is among the values of frequency previously found in other places from our country [7][8][9]30,31 and relatively similar with other studies from other Latin American countries 2,3,21,27 .…”
Section: Discussionsupporting
confidence: 93%
“…In Peru, a few reports have informed of frequencies from 7.8% to 44.92% in rural populations from different places [7][8][9]19,30,31 . However, seroepidemiological studies about human toxocariasis in Peruvian Amazonian populations have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while some researchers have verified either an increase of the toxocariasis prevalence in the male population [20,21] , others have shown that females are more closely associated with the zoonosis [8] . No association between gender and an ELISA positive result for toxocariasis has also been observed [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Infections with the organism are spread worldwide and it is often the most frequently isolated protozoan in parasitological surveys (2)(3)(4). In developing countries, B. hominis has higher prevalence (30-50%) in comparison with developed countries (1.5-10%) (5,6).…”
Section: Introductionmentioning
confidence: 99%